KEBIJAKAN PENYELESAIAN PELANGGARAN BERAT HAM MASA LALU OLEH PEMERINTAHAN JOKOWI - Ahmad Hambali (Collegium Studiosum Journal, 2023)
President Jokowi has included a policy to resolve past gross human rights violations in the two 2014-2024 RPJMN periods. Even though it has only been established 8 years since being elected by issuing Presidential Decree No. 17 of 2022, Presidential Decree No. 4 No. 2023 and Presidential Instruction No. 2 of 2023.This research is aimed to exploring the policies of the Jokowi government in resolving the past gross human rights violations from the beginning to the present, including finding at the advantages and disadvantages. The research method used a qualitative, descriptive approach by examining emerging policies and viewing and analyzing a series of regulations related to their relationship with the implementation of policies in the field. From this research obtained the wall of impunity is still roled to intervence a process, lack of understanding and half-hearted management to resolve the past gross human rights violations gripped the government's steps. Not to mention the existence of sabotage and stowaways to resolve the gross violations of human rights, whether they were aware of it or not within the palace. passed various existing regulations for resolve of the past gross human rights violations.